Shan Sdn Bhd: Grated Coconut And Milk Machine / Muhammad Syazmim Awang ...[et al.] - Awang, Muhammad Syazmim; Adam, Muhammad Haziq; Roslan, Amreel Syamim; Aziz, Natasha Amirah (2019)
SHAN Sdn Bhd offers machine products and services for customers, providing a grated coconut and milk machine in a short period that gives high satisfaction of consumer. Our client is retailer because they will be used a lot of coconut, so it can help them to save time and energy in order to produce grated coconut and coconut milk. we are also targeting our product amongst the society by introducing it with affordable price. SHAN Sdn. Bhd offers a machine that can produce a natural coconut milk with no prohibited or harmful substance because it extracts from original coconut and no adding other ingredients.